Communicating Under the Regimes of Divergent Ideas: How Public Agencies in Sweden Manage Tensions Between Transparency and Consistency. (November 2019) - Fredriksson, Magnus; Edwards, Lee
In this article we draw on Scandinavian institutionalism to argue that ideas act as imperatives for organizations' communication, whereby differences between ideas can generate tensions that organizations must manage. We focus on transparency and consistency, ideas that frequently underpin organizational communication, but are mobilized by different problems and offer different solutions. An analysis of communication policy and strategy documents in 188 Swedish public agencies shows how transparency and consistency coexist, but are translated into local settings in divergent ways. The resulting tensions relate to the purpose of communication, roles of organizational actors and of media, and stakeholder identities. Tensions are managed using three strategies: firewalling, ranking, and compromising. The findings show that ideas are fundamental to organizational communication, but that organizations also contribute to transformations and hybridizations of ideas. We suggest further analyses of interactions among institutions, organizations, and communication, particularly of how the translations of ideas generate tensions that must be resolved.